Decrease in ultrasound Brain Tissue Pulsations as a potential surrogate marker of response to antidepressant. (February 2022) - Desmidt, Thomas; Dujardin, Paul-Armand; Brizard, Bruno; Réméniéras, Jean-Pierre; Gissot, Valérie; Dufour-Rainfray, Diane; Atanasova, Boriana; Kazour, François; Belzung, Catherine; Camus, Vincent; El-Hage, Wissam
Abstract: Previous cross-sectional studies found excessive Brain Tissue Pulsations ( BTP) in mid-life depression, which could constitute a mechanism of brain damage in depression. However, it remains unclear whether successful antidepressant therapy restores BTP amplitudes. In this prospective study, we investigated longitudinal changes in BTP in patients with a major depressive episode (MDE), among responders and non-responders to escitalopram. Fifty-two individuals with a MDE, free of antidepressants at baseline, were included in an 8-week open-labeled escitalopram trial. Ultrasound Tissue Pulsatility Imaging (TPI) was applied to measure resting BTP and BTP reactivity in an orthostatic challenge, at baseline and at week 8. TPI data were available for 48 participants divided into responders (n = 28, 58.3%) and non-responders (n = 20, 41.7%) according to change in the MADRS score. MaxBTP significantly decreased between baseline and week 8, only in responders. In addition, changes in MaxBTP during the orthostatic challenge were no longer significant at week 8 but only in responders. Because excessive BTP constitutes a potential mechanism for brain damage, our results suggest that a successful pharmacotherapy could benefit patients to lower the risk of brain damage in individuals with depression, a population exposed to stroke, small arteries disease and brain atrophy. TPI could provide a surrogate biomarker to monitor antidepressant response and brain health in depression in clinical routine. Highlights: Excessive Brain Tissue Pulsations (BTP) was previously observed in depression. We investigated prospective changes in BTP in an 8-week escitalopram trial. We found that BTP decreased with successful pharmacotherapy. Besides, BTP reactivity with orthostasis was no longer significant in responders. BTP may provide a neuroimaging marker for monitoring brain health in depression.